Badger, Ed., Ideas That Work In College Teaching - Duffy, Eve (Teaching History: A Journal of Methods, 2009)
This book of articles by professors from a wide range of disciplines at SUNY Potsdam is a pleasure and a great source of practical guidance and information . The scholars who came together to write the book are engaged-teaching twelve hours each semester, working on freshman seminars, and actively involved in a reflective practice . It was out of this practice that the book emerged: Professors from thirteen different disciplines- art, biology, computer science, education, geology, history, math, modern languages, philosophy, physics, politics, psychology, and sociology-had been reading books on education, and after reading one book that enraged the group, those gathered agreed that they could do better. The volume works especially well because it includes teachers from one institution with a set body of students, most of whom come from working class background in which "education has been neither a top personal nor a family priority," and the faculty from one institution engage their students.